The Effectiveness of Quizwhizzer to Learning Qira’ah Students’ at Islamic High School Abadiyah Pati - Shondaqh, Angelina; Annas, Azwar (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Learning media is important to meet the needs of students in the learning process in order to achieve a learning goal. This study aims to determine students' perceptions of the use of quizwhizzer media in learning maharah qira'ah, to determine the maharah qira'ah ability of students before and after using quizwhizzer platform media, and to test and prove the effectiveness of quizwhizzer platform media used in learning maharah qira'ah. This research uses a pre-experimental quantitative approach with a one group pretest-posttest research design. The data collection methods used in this study were questionnaires and tests. The data analysis technique used in this research is descriptive statistical analysis and interferential statistical analysis including data normality test, t test (paired sample t test), N-Gain test (effectiveness). The findings of this study state that there is a difference between pretest scores smaller than posttest scores with an average of 30.97 <83.27. These results are also said to have increased by looking at the level of significance through the paired sample t test (sig 0.000 <0.05, then Ha is accepted). The percentage obtained from the N-Gain test shows 75.49% through the basis of decision making categorized as “quite effective”. It can be concluded that the use of quizwhizzer platform media in learning maharah qira'ah is proven to be able to improve maharah qira'ah. And the quizwhizzer media platform is “quite effective” to be used as a medium or evaluation of maharah qira'ah learning. Learning using gamification-based media such as QuizWhizzer makes a positive contribution to learning by creating a more interesting and interactive learning experience. This has an impact on the achievement of more optimal learning objectives. Therefore, QuizWhizzer can be used as an effective learning or evaluation media in teaching maharah qira'ah.